Development of high resolution melting analysis for the diagnosis of human malaria - Chua, Kek Heng; Lim, Siew Chee; Ng, Ching Ching; Lee, Ping Chin; Lim, Yvonne Ai Lian; Lau, Tze Pheng; Chai, Hwa Chia (Nature Publishing Group, 2015)
Molecular detection has overcome limitations of microscopic examination by providing greater sensitivity and specificity in Plasmodium species detection. The objective of the present study was to develop a quantitative real-time polymerase chain reaction coupled with high-resolution melting (qRT-PCR-HRM) assay for rapid, accurate and simultaneous detection of all five human Plasmodium spp. A pair of primers targeted the 18S SSU rRNA gene of the Plasmodium spp. was designed for qRT-PCR-HRM assay development. Analytical sensitivity and specificity of the assay were evaluated. Samples collected from 229 malaria suspected patients recruited from Sabah, Malaysia were screened using the assay and results were compared with data obtained using PlasmoNexTM, a hexaplex PCR system. The qRT-PCR-HRM assay was able to detect and discriminate the five Plasmodium spp. with lowest detection limits of 1–100 copy numbers without nonspecific amplifications. The detection of Plasmodium spp. in clinical samples using this assay also achieved 100% concordance with that obtained using PlasmoNexTM. This indicated that the diagnostic sensitivity and specificity of this assay in Plasmodium spp. detection is comparable with those of PlasmoNexTM. The qRT-PCR-HRM assay is simple, produces results in two hours and enables high-throughput screening. Thus, it is an alternative method for rapid and accurate malaria diagnosis.